Spontaneous poisoning by Baccharis vulneraria Backer in cattle - Costa L.S.* (2022)
© 2022 Colegio Brasileiro de Patologia Animal. All rights reserved.Baccharis vulneraria Backer is a sub-shrub frequently found in southern Brazil, which leads to gastrointestinal tract intoxication. The objective of this study is to describe epidemiological, clinical and anatomopathological aspects of two cases of B. vulneraria poisoning in cattle. Two bovines from two different municipalities in the Itajaí Valley, Santa Catarina, Brazil were necropsied and performed the histopathological evaluation and botanical classification of the plant found in the pasture. Bovine 1 had dehydration, ruminal atony, diarrhea, congested mucous membranes and hypothermia for 20 hours, and died during clinical care. At necropsy, there was moderate multifocal detachment and reddening of the forestomachs mucosa. Bovine 2 presented anorexia, dry feces, ruminal atony, vocalization and muscle tremors for ten days, unresponsive to treatments, evolving to death. At necropsy were seen loosening of the mucosa with marked diffuse reddening and transmural edema. The microscopic exam revealed degeneration, necrosis, vesiculation, and detachment of the forestomachs' mucosa, associated with moderate multifocal neutrophilic infiltrate (Bovine 1); marked diffuse transmural necrosis, edema, hemorrhage, and marked fibrinous exudation (Bovine 2). A large amount of B. vulneraria was found in the pastures, with signs of consumption. In this report, a case of subacute evolution of B. vulneraria poisoning was observed, since the poisoning by this plant is usually acute. More knowledge about poisoning by this plant is necessary for the prevention and control, avoiding new mortality cases.